2023
DOI: 10.3389/fendo.2022.1073261
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of endometrioma on ovarian aging from basic science to clinical management

Abstract: Endometriosis is a common reproductive disorder characterized by the presence of endometrial implants outside of the uterus. It affects ~1 in 10 women of reproductive age. Endometriosis in the ovary, also known as endometrioma (OMA), is the most frequent implantation site and the leading cause of reproductive failure in affected women. Ovarian aging is one of the characteristic features of OMA, however its underlying mechanism yet to be determined. Accumulated evidence has shown that pelvic and local microenvi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 182 publications
0
2
0
Order By: Relevance
“…Significantly shorter AGDs (for AGD-AF, AGD-AC, or both) have also been associated with four correlates of endometriosis: premature ovarian insufficiency [34,35], dysmenorrhea [36,37], reduced responses to ovarian stimulation in IVF [29,38], and relatively regular menstrual cycles [39]. These findings support the hypothesis of causal links between lower prenatal testosterone and higher risk of endometriosis, as does evidence suggesting that women with endometriosis exhibit a higher level of sexual difference from males than do healthy women for a suite of sexually dimorphic traits [40].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Significantly shorter AGDs (for AGD-AF, AGD-AC, or both) have also been associated with four correlates of endometriosis: premature ovarian insufficiency [34,35], dysmenorrhea [36,37], reduced responses to ovarian stimulation in IVF [29,38], and relatively regular menstrual cycles [39]. These findings support the hypothesis of causal links between lower prenatal testosterone and higher risk of endometriosis, as does evidence suggesting that women with endometriosis exhibit a higher level of sexual difference from males than do healthy women for a suite of sexually dimorphic traits [40].…”
Section: Discussionmentioning
confidence: 99%
“…Significantly shorter AGDs (for AGD-AF, AGD-AC, or both) have also been associated with four correlates of endometriosis: premature ovarian insufficiency [34,35], dysmenorrhea [36,37],…”
Section: (Which Was Not Certified By Peer Review)mentioning
confidence: 99%
“…One study reported an increased risk of early natural menopause (< 45 years) in endometriosis patients [ 40 ]. Potential mechanisms include effects of endometrioma (endometriosis on the ovary) on ovarian function, effects of surgical excision of endometrioma [ 41 ] and effects of endometriosis-related traits such as reduced body mass index [ 39 ]. The attenuation of the effect of endometriosis PRS on age at menopause when endometriosis cases were excluded may point to effects of lesion presence on age at menopause, but further validation is needed.…”
Section: Discussionmentioning
confidence: 99%
“…Normally, a single follicle achieves full maturation to release an oocyte during each menstrual cycle, and this is regulated meticulously using hormones such as gonadotropins [6]. The importance of OR extends into various facets of reproductive medicine [7,8]. It not only informs the biological timeline for a woman's fertility, but it also serves as a critical parameter in assessing and planning the management of infertility.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is well documented that certain pathological conditions, including endometriosis, disrupt normal follicular activation and maturation, thereby contributing to ovarian dysfunction and a consequential decline in OR. Women with endometriosis, particularly those of advanced age, are at a heightened risk of reduced OR compared to their younger, healthy counterparts [7,8]. The mechanisms instigating this decline-particularly in the context of endometriosis-are not yet fully elucidated, and they continue to be the subject of comprehensive scientific inquiry.…”
Section: Introductionmentioning
confidence: 99%